Electrolyte, lithium ion battery and electric equipment
By using specific proportions of pyridazine compounds and DFEA in lithium battery electrolytes, the problems of poor stability of electrolyte additives and affecting cycle life are solved, and the efficient charging and discharging of the battery and the improvement of low-temperature performance are achieved.
Patent Information
- Application Number
- CN202411625870.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
In the prior art, in order to improve the charge and discharge rate and low temperature performance of lithium batteries, the use of electrolyte additives has problems such as poor stability and affecting cycle life.
An electrolyte containing pyridazine compounds and difluoroethyl acetate (DFEA) is provided. By adjusting its proportion in the electrolyte, the conductivity and antioxidant capacity of the electrolyte are significantly improved.
It improves the transmission rate of lithium ions, improves the low-temperature performance and charge and discharge rate of the battery, and extends the cycle life of the battery, avoiding the problem of oxidation and deterioration of the electrolyte at high voltage.
Smart Images

Figure BDA0005134719800000021 
Figure BDA0005134719800000022 
Figure BDA0005134719800000031
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an electrolyte, a lithium-ion battery and an electrical device. Background Art
[0002] Lithium batteries, as the heart of modern technology, have penetrated into every aspect of our daily lives and become an indispensable energy pillar. They not only drive our smartphones and laptops, but also power electric vehicles and even play an important role in medical devices and wearable technologies. With the advancement of technology, the demand for high-rate charging and discharging (i.e. fast charging and discharging) is growing, not only to meet the demanding requirements of high-power tools, but also to maintain the performance and reliability of equipment under extreme low temperature conditions.
[0003] However, despite the remarkable achievements in lithium battery technology, the current battery charge and discharge rates and low temperature performance still face certain limitations. In order to overcome these limitations, researchers and engineers are actively exploring various innovative methods, among which improving the conductivity of the electrolyte is considered to be one of the key ways to solve this problem. By optimizing the chemical composition and structure of the electrolyte, the migration rate of lithium ions inside the battery can be significantly increased, thereby achieving faster charge and discharge speeds and improving the overall performance of the battery. However, the use of electrolyte additives will face problems such as poor stability and reduced cycle life. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of the prior art such as poor stability and impact on cycle life of electrolyte additives in order to improve the battery charge and discharge rate and low temperature performance, thereby providing an electrolyte, a lithium-ion battery and an electrical device.
[0005] To this end, this application provides the following technical solutions:
[0006] According to one aspect of the present application, an electrolyte is provided, comprising: a pyridazine compound and difluoroethyl acetate (DFEA, CAS No. 1550-44-3), wherein the pyridazine compound accounts for A% of the total mass of the electrolyte, 2≤A≤70; and the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 2≤D≤30.
[0007] In some optional embodiments, the pyridazine compound accounts for A% of the total mass of the electrolyte, 5≤A≤30;
[0008] And / or, the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 5≤D≤20.
[0009] In some optional embodiments, the pyridazine compound has the following structure:
[0010]
[0011] Wherein, R1, R2, R3, R4 are independently selected from at least one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aromatic, substituted or unsubstituted carbonyl, and substituted or unsubstituted ester.
[0012] In some optional embodiments, the pyridazine compound has any of the following structures:
[0013]
[0014]
[0015] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.
[0016] In some optional embodiments, the lithium-ion battery includes an electrode sheet and a separator, and a total of B pole tabs are arranged in the length direction of the electrode sheet, where B≥3; preferably, 3≤B≤50.
[0017] In some optional embodiments, the electrode sheet has two surfaces arranged opposite to each other in its own thickness direction, wherein at least one surface is provided with a plurality of recesses, the depth of the recesses is 1-150 μm, the diameter is C μm, 5≤C≤100, and the spacing between the recesses is 20-500 μm.
[0018] In some optional embodiments, the diameter C μm of the concave portion and the percentage of the pyridazine compound in the total mass of the electrolyte A% satisfy the relationship: 0.5≤C / A≤20.
[0019] In some optional embodiments, the electrode sheet includes a positive electrode sheet and a negative electrode sheet, the negative electrode sheet includes a negative electrode active material, the negative electrode active material contains silicon, and the mass percentage of silicon in the negative electrode active material is F%, 1≤F≤30; preferably, 5≤F≤20.
[0020] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned lithium-ion battery.
[0021] The technical solution of this application has the following advantages:
[0022] The electrolyte provided in the present application includes: pyridazine compounds and difluoroethyl acetate (DFEA), wherein the pyridazine compounds account for A% of the total mass of the electrolyte, 2≤A≤70; the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 2≤D≤30. In the present application, a specific amount of pyridazine compounds is used in combination with DFEA, which can significantly improve the overall conductivity of the electrolyte, reduce the resistance to ion transmission, promote the efficient transmission of lithium ions inside the battery, and improve the low temperature performance and charge and discharge rate of the battery; at the same time, the antioxidant capacity of the electrolyte is also improved, so that the electrolyte can still remain stable under high voltage, avoiding the problem of poor antioxidant properties of the electrolyte and affecting the battery cycle performance caused by the introduction of additives. Specifically, pyridazine compounds, as a unique small molecule solvent, have an aromatic structure, in which two electronegative nitrogen atoms are arranged in adjacent positions, and this polarity is concentrated on the same side of the aromatic ring, further enhancing the polarity of the molecule. This structural feature makes the dielectric constant of pyridazine compounds extremely high, which is beneficial to improve the solvation ability of lithium ions in the electrolyte, thereby enhancing the conductivity of the electrolyte. At the same time, the intermolecular interaction force of aromatic pyridazine compounds is weak, which leads to their lower viscosity, providing convenient conditions for the rapid migration of lithium ions in the electrolyte. In the electrolyte, pyridazine compounds as solvents or partial solvents can significantly improve the overall conductivity of the electrolyte, reduce the resistance to ion transmission, and promote the efficient transmission of lithium ions inside the battery. It can ensure that the battery's charge and discharge capacity retention rate at high rates is improved, ensure that the battery operates stably under low temperature conditions, and reduce lithium precipitation. As a small molecule solvent, DFEA has high polarity and low viscosity. When a specific amount of DFEA and pyridazine compounds are used as electrolyte solvents together, the electrolyte has a high conductivity. At the same time, due to the substitution of fluorine atoms, DFEA has strong antioxidant ability and can remain stable under high voltage. By adding DFEA to the electrolyte, the antioxidant property of the electrolyte can be significantly improved, avoiding the problem of poor antioxidant property of the electrolyte introduced by pyridazine compounds, thereby ensuring that the electrolyte can remain stable for a long time at high rate and high voltage, and the battery capacity decreases less over a long period of time.
[0023] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0024] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0025] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0026] According to one aspect of the present application, an electrolyte is provided, comprising: a pyridazine compound and difluoroethyl acetate (DFEA), wherein the pyridazine compound accounts for A% of the total mass of the electrolyte, 2≤A≤70; the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 2≤D≤30. As an example, the pyridazine compound accounts for 2%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70% of the total mass of the electrolyte, or within the range of any of the above values; the difluoroethyl acetate accounts for 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30% of the total mass of the electrolyte, or within the range of any of the above values.
[0027] As described in the background technology, electrolyte additives are used to improve the charge and discharge rate and low temperature performance of the battery, and the use of electrolyte additives will face problems such as poor stability and affecting the cycle life. In order to solve the above problems, the present application provides an electrolyte comprising a specific amount of pyridazine compounds and difluoroethyl acetate, wherein the pyridazine compounds, as a unique small molecule solvent, have an aromatic structure, wherein two electronegative nitrogen atoms are arranged in ortho positions, and such polar atoms (two electronegative nitrogen atoms) are concentrated on the same side of the aromatic ring, further enhancing the polarity of the molecule. On the one hand, this structural feature makes the dielectric constant of pyridazine compounds extremely high, which is conducive to improving the solvation ability of lithium ions in the electrolyte, thereby enhancing the conductivity of the electrolyte, which is conducive to reducing the transmission resistance of lithium ions and improving the charge and discharge rate of the battery; on the other hand, the intermolecular interaction force of aromatic pyridazine compounds is weak, resulting in a smaller viscosity characteristic, which ensures that lithium ions can achieve faster migration even at lower temperatures, that is, using aromatic pyridazine compounds as solvents or partial solvents for electrolytes can provide convenient conditions for the rapid migration of lithium ions under low temperature conditions, which is conducive to improving the low temperature performance of the battery and avoiding the occurrence of lithium precipitation. If the amount of pyridazine compounds added is less than 2%, there is no improvement in the overall conductivity of the electrolyte, and there is no improvement in the charge and discharge rate and low temperature performance of the battery; if the amount of pyridazine compounds added is greater than 70%, the overall oxidation resistance of the electrolyte is greatly reduced, and the electrolyte will be oxidized and deteriorated in large quantities during the battery cycle, especially at high voltage, and the capacity retention rate will be greatly reduced. The high voltages mentioned in this scheme are all voltages ≥4.5V.
[0028] DFEA, as a small molecule solvent, has extremely high antioxidant properties and can exist stably for a long time under high voltage. Therefore, it is often used as a solvent for high-voltage electrolytes. When DFEA is added to an electrolyte containing pyridazine compounds, the antioxidant stability of the electrolyte can be greatly improved, which greatly compensates for the poor antioxidant capacity of pyridazine compound molecules, allowing the electrolyte as a whole to be stably stored for a longer time under high voltage, and the battery to be stably cycled for a longer time under high voltage. When the amount of DFEA added is less than 2%, due to the small amount added, its antioxidant ability cannot be exerted, and the high-voltage performance of the battery cannot be improved; when the amount of DFEA added is greater than 30%, due to its higher viscosity, the overall viscosity of the electrolyte increases, the conductivity decreases, and the battery cycle performance decreases.
[0029] In some optional embodiments, the pyridazine compound accounts for A% of the total mass of the electrolyte, 5≤A≤30;
[0030] And / or, the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 5≤D≤20.
[0031] In the present application, by adjusting the proportions of pyridazine compounds and difluoroethyl acetate (DFEA) in the electrolyte, the advantages of both can be fully utilized to improve the battery charge and discharge rate and low temperature performance, while also improving the battery cycle life.
[0032] In some optional embodiments, the pyridazine compound has the following structure:
[0033]
[0034] Wherein, R1, R2, R3, and R4 are independently selected from at least one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aromatic, substituted or unsubstituted carbonyl, and substituted or unsubstituted ester; optionally, C1-C5 substituted or unsubstituted alkyl, C2-C5 substituted or unsubstituted alkenyl, C2-C5 substituted or unsubstituted alkynyl, C3-C8 substituted or unsubstituted aromatic, C At least one of a C1-C5 substituted or unsubstituted carbonyl group, a C1-C5 substituted or unsubstituted ester group, wherein the substituents in the substituted alkyl group, substituted alkenyl group, substituted alkynyl group, substituted aromatic group, substituted carbonyl group and substituted ester group include at least one of a methyl group, a trifluoromethyl group, an ethyl group, a trifluoroethyl group, a propyl group, an isopropyl group, an alkenyl group, an allyl group, an alkynyl group, a propargyl group, a phenyl group, an acetyl group and a methoxyacetyl group; and the aromatic group may also include at least one heteroatom selected from the group consisting of N, O and S.
[0035] In some optional embodiments, the pyridazine compound has any of the following structures:
[0036]
[0037]
[0038] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned electrolyte.
[0039] In the present application, the electrolyte used in the lithium-ion battery contains a specific amount of DFEA and pyridazine compounds, which can promote the efficient transmission of lithium ions inside the battery, ensure that the battery's charge and discharge capacity retention rate at high rates is improved, ensure that the battery operates stably under low temperature conditions, reduce lithium precipitation, and ensure that the battery can remain stable for a long time at high rates and high voltages, and the battery's long-term cycle capacity decreases less.
[0040] In some optional embodiments, the lithium-ion battery includes an electrode sheet and a diaphragm, and a total of B pole tabs are arranged in the length direction of the electrode sheet, B≥3; preferably, 3≤B≤50; as an example, the number of pole tabs arranged in the length direction of the electrode sheet is 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or within the range of any of the above values. The lithium-ion battery provided in the present application increases the number of contact points of the battery by increasing the number of pole tabs, thereby improving the current transmission efficiency and the overall conductivity of the battery; this design can make the current more evenly distributed during the transmission process, reduce the internal resistance and heat generation of the battery during high-rate charge and discharge, and help prevent the battery from overheating during high-power output, thereby extending the battery life and improving its safety.
[0041] In some optional embodiments, the electrode sheet has two surfaces arranged opposite to each other in its own thickness direction, wherein at least one surface is provided with a plurality of recesses, the depth of the recesses is 1-150 μm, the diameter is C μm, 5≤C≤100, and the spacing of the recesses is 20-500 μm. As an example, the depth of the recesses is 1 μm, 5 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, or within the range of any of the above values; the diameter of the recesses is 5 μm, 8 μm, 20 μm, 50 μm, 70 μm, 85 μm, 100 μm, or within the range of any of the above values. The spacing of the recesses is 20 μm, 40 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 300 μm, 500 μm, or within the range of any of the above values.
[0042] The present application does not limit the shape of the concave portion, for example, the shape of the concave portion can be a triangle, a rhombus, a circular hole, or a square; it should be noted that the diameter of the concave portion refers to the diameter of the circumscribed circle of the concave portion. The preparation method of the concave structure is conventional in the field, for example, it can be prepared by physical engraving, embossing, or chemical etching.
[0043] In the present application, the conductivity of lithium ions in the electrolyte using pyridazine compounds is greatly improved, that is, the transmission speed of lithium ions between the positive and negative electrodes is greatly improved. However, after the battery is transmitted to the positive and negative electrodes, it still needs to go through the process of entering the pole piece. If it cannot enter smoothly in time, it will cause problems such as lithium precipitation. After the recessed structure is introduced on the surface of the pole piece, the diffusion distance of lithium ions in the electrode sheet (positive and negative pole piece) can be significantly reduced, the large accumulation of lithium ions can be avoided, lithium precipitation can be reduced, and the battery life can be extended. In addition, thick and high-density pole pieces often have wetting problems. It is difficult for the inside of the pole piece to contact the electrolyte and cannot play a role. The setting of the recessed structure can solve this problem well. The presence of these recesses can make the electrolyte directly contact the deep part of the pole piece, thereby improving the wetting performance of the pole piece, so that the pole piece with higher thickness and higher density can be used in the battery. The use of electrode pore-making technology to prepare recesses can also improve / reduce the degradation of battery performance caused by the compaction and thickness inconsistency of the pole piece, reduce the uneven battery performance caused by uneven coating, and make the battery more stable during the cycle.
[0044] In some optional embodiments, the diameter Cμm of the recess and the percentage of pyridazine compounds in the total mass of the electrolyte A% satisfy the relationship: 0.5≤C / A≤20. As an example, the C / A ratio can be 0.5, 1, 2, 5, 8, 10, 13, 15, 18, 20, or within the range of any of the above values. The present application facilitates electrolyte infiltration by regulating C / A within this range, improves the transmission rate of lithium ions, and improves the fast charging performance of the battery. If the C / A value is too large, it means that the concave diameter is too large, the density is low and / or the pyridazine compound content is low, which means that the number of holes is small and the pyridazine compound with a low content cannot fully exert its wettability effect; if C / A is too small, the concave diameter is small, the density is high and / or the pyridazine compound content is high, which means that the surface area of the electrode is increased, and the SEI may not be able to completely cover the surface of the electrode, causing the active material of the electrode to be in direct contact with the electrolyte and be oxidized and decomposed. At the same time, the oxidation resistance of the pyridazine compound itself is poor. A large amount of pyridazine compounds in full contact with the electrode will cause the pyridazine compounds to undergo oxidative decomposition, further accelerating the deterioration of the electrolyte and deteriorating the battery performance.
[0045] In some optional embodiments, the electrode sheet includes a positive electrode sheet and a negative electrode sheet, the negative electrode sheet includes a negative electrode active material, the negative electrode active material contains silicon, and the mass percentage of silicon in the negative electrode active material is F%, 1≤F≤30; preferably, 5≤F≤20. As an example, the mass percentage of silicon in the negative electrode active material is 1%, 3%, 5%, 8%, 10%, 13%, 15%, 17%, 20%, 23%, 25%, 28%, 30%, or within the range of any of the above values. The use of pyridazine compounds as solvents can increase the conductivity of the electrolyte and improve the fast charging performance of the battery. However, in addition to the influence of conductivity on the fast charging performance of the battery, the fast charging performance is also related to the infiltration and penetration of the positive and negative electrode electrolytes, especially the high energy density battery system. When using traditional graphite as the negative electrode, due to the energy density limitation of graphite itself, a higher thickness and compaction will be required, which will further aggravate the problem of electrolyte infiltration. The difference is that the theoretical energy density of silicon-based negative electrode materials is large, so the thickness of the electrode coating and the compaction density of the electrode can be appropriately reduced. This is conducive to the electrolyte being able to better infiltrate the negative electrode, avoiding it becoming the rate-limiting step in the fast charging process and avoiding problems such as interface lithium plating.
[0046] As an example, the negative electrode active material described in the present application can be a silicon-carbon composite material, including a shell layer and a core, the core includes a silicon-based material and a porous carbon material; the shell layer includes at least one of a carbon material, silicon monoxide, silicon dioxide and lithium silicate.
[0047] In some optional embodiments, the mass of the core accounts for 40% to 65% of the total mass of the negative electrode active material; the mass of the shell accounts for 35% to 60% of the total mass of the negative electrode active material.
[0048] According to another aspect of the present application, there is provided an electric device, comprising the above-mentioned lithium-ion battery. The lithium-ion battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0049] Typically, the electrolyte described in the present application is a non-aqueous electrolyte, and the electrolyte contains, in addition to pyridazine compounds and DFEA, an organic solvent and a lithium salt; and may also include other functional additives. Among them, the organic solvent can be selected from carbonates and / or carboxylates, the carbonate solvent can be selected from ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and one or more of the fluorinated compounds of the above solvents, and the carboxylate solvent can be selected from ethyl acetate (EA), propyl acetate, n-butyl acetate, isobutyl acetate, methyl propionate (MP), propyl propionate (PP), ethyl propionate (EP), methyl butyrate, ethyl butyrate and one or more of the fluorinated compounds of the above solvents. The additives include one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), succinonitrile (SN), adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTCN), fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), etc.
[0050] In the present application, the lithium salt can be selected from the electrolyte lithium salts conventionally used in the art, including lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium 4,5-dicyano-2-trifluoromethylimidazole (LiDTI), lithium difluorophosphate (LiPO2F2), and one or more of lithium difluorobis(oxalatophosphate).
[0051] In the present application, the composition and preparation method of the lithium-ion battery are conventional in the field except for the above-mentioned limitations. As an example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The material, composition and manufacturing method of the positive electrode sheet used in the lithium-ion battery of the present application may include any technology disclosed in the prior art.
[0052] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder.
[0053] As an example, in the present application, the mass percentage of each component in the positive electrode active material layer is: 80-99.8wt% of positive electrode active material, 0.1-10wt% of conductive agent, 0.1-10wt% of binder. Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6wt% of positive electrode active material, 0.2-5wt% of conductive agent, 0.2-5wt% of binder.
[0054] In the present application, the mass percentage of each component in the negative electrode active material layer is: 80-99.8wt% of negative electrode active material, 0.1-10wt% of conductive agent, 0.1-10wt% of binder. Preferably, the mass percentage of each component in the negative electrode active material layer is: 90-99.6wt% of negative electrode active material, 0.2-5wt% of conductive agent, 0.2-5wt% of binder.
[0055] In the present application, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder. The binder is selected from at least one of sodium carboxymethyl cellulose, styrene butadiene latex, polytetrafluoroethylene, and polyethylene oxide.
[0056] In the present application, the positive electrode active material is selected from one or more of transition metal lithium oxide, lithium iron phosphate, and lithium manganate; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M 1-y-z O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0057] The material and shape of the separator used in the lithium ion battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.
[0058] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. Various experiments and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "%" refers to mass percentage.
[0059] Test methods and equipment:
[0060] 1. Conductivity: The electrolyte was tested at 25°C using a conductivity meter. The conductivity meter model was Mettler S230.
[0061] 2. Viscosity: The electrolyte was tested at 25°C using a viscometer, the model of which was Austrian Anton Paar rotational rheometer mcr92.
[0062] 3. 25℃ cycle performance test:
[0063] The lithium ion battery prepared in the embodiment and the comparative example was charged and discharged for 500 weeks at 25°C at a rate of 5C within the charge and discharge cut-off voltage range (charge and discharge range of 3.0-4.5V), and the discharge capacity of the first week was measured as x1 mAh, and the thickness of the tested lithium ion battery was y1 cm; the discharge capacity of the 500th week was measured as x2 mAh, and the thickness of the lithium ion battery after the 500th week was y2 cm. The capacity of the 500th week was divided by the capacity of the 1st week to obtain the cycle capacity retention rate of the 500th week R1=100%·x2 / x1; the thickness of the lithium ion battery after the 500th week was subtracted from the thickness of the 1st week, and then divided by the thickness of the first week to obtain the battery thickness expansion rate of the 500th week H1=100%·(y2-y1) / y1.
[0064] 4. 10℃ cycle performance test:
[0065] The battery prepared in the embodiment and the comparative example was charged and discharged for 500 weeks at 10°C at a rate of 2C within the charge and discharge cut-off voltage range (charge and discharge range of 3.0-4.5V), and the discharge capacity of the first week was measured as x3mAh, and the thickness of the tested lithium-ion battery was y3 cm; the discharge capacity of the 500th week was measured as x4 mAh, and the thickness of the lithium-ion battery after the 500th week was y4 cm. The capacity of the 500th week was divided by the capacity of the first week to obtain the cycle capacity retention rate of the 500th week R2 = 100% x4 / x3; the thickness of the lithium-ion battery after the 500th week was subtracted from the thickness of the first week, and then divided by the thickness of the first week to obtain the battery thickness expansion rate H2 = 100% (y4-y3) / y3 at the 500th week.
[0066] 5. Temperature rise during fast charging:
[0067] The lithium-ion batteries prepared in the embodiments and comparative examples were charged and discharged for 50 weeks at 25°C at a rate of 10C within the charge and discharge cut-off voltage range (charge and discharge range is 3.0-4.5V). The temperature of the battery surface in the first week of the test was T1°C, and the temperature of the battery surface in the 50th week was T2°C. The temperature rise of the battery during fast charging was T=T2-T1°C.
[0068] 6. Lithium precipitation test:
[0069] The battery prepared in the embodiment and the comparative example was charged to 4.5V at 8C constant current and constant voltage at 25°C, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 50 cycles, the battery was fully dissected and the lithium precipitation was observed. The degree of lithium precipitation was from light to heavy, which was no lithium precipitation, slight lithium precipitation, lithium precipitation and severe lithium precipitation. After disassembly, there was no obvious lithium metal deposit on the electrode surface, the surface was smooth, and no lithium dendrites were formed, which was determined to be no lithium precipitation; after disassembly, there was a small amount of lithium metal deposit on the electrode surface, but the lithium dendrites were not obvious, which was determined to be slight lithium precipitation; after disassembly, there was obvious lithium metal deposit and lithium dendrite formation on the electrode surface, which was determined to be lithium precipitation; after disassembly, there was a large amount of lithium metal deposit and lithium dendrite formation on the electrode surface, which might even cause safety problems such as battery short circuit or thermal runaway, which was determined to be severe lithium precipitation.
[0070] Example 1
[0071] This embodiment provides an electrolyte, and its specific composition and preparation method are as follows:
[0072] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC / PC / DEC / PP were mixed evenly according to (10:10:40:20) (specific composition see Table 1), then A% of pyridazine compounds based on the total mass of the electrolyte and D% of DFEA based on the total mass of the electrolyte were added, and then 14% of fully dried lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte was quickly added, and after dissolution, 3% of polynitrile compounds (succinonitrile) based on the total mass of the electrolyte and 12wt% of fluoroethylene carbonate were added. After stirring evenly, the desired electrolyte was obtained after passing the moisture and free acid tests.
[0073] Example 2-Example 16
[0074] The only difference from Example A is the specific selection and dosage of the pyridazine compound and the dosage of DFEA, see Table 1 for details.
[0075] Comparative Example 1-Comparative Example 4
[0076] The only difference from Example A1 is that the specific dosage of the pyridazine compound and the dosage of DFEA are different, see Table 1 for details.
[0077] Table 1
[0078]
[0079] Note: “ / ” in the table means that the component is not added.
[0080] The electrolytes provided in the above embodiments and comparative examples were tested for conductivity and viscosity. The specific test results are shown in Table 2:
[0081] Table 2
[0082]
[0083]
[0084] From the data in the above table, it can be seen that when pyridazine and DFEA are used as solvents, the conductivity of the electrolyte will be significantly improved and the viscosity will be significantly reduced within the optimal range.
[0085] Example E1
[0086] This embodiment provides a lithium ion battery, and its specific composition and preparation method are as follows:
[0087] (1) Preparation of positive electrode
[0088] The positive electrode active material lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotube (CNT) are mixed in a ratio of 8:1:0.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity (solid content 75%); the positive electrode active slurry is evenly coated on both surfaces of the aluminum foil, and the coating amount is 0.33g / 1500mm 2 .
[0089] After drying, rolling, cutting, cleaning and pore formation using a laser device, regularly distributed cylindrical recesses are formed on the surface of the positive electrode. The depth of the cylindrical recesses is 20 μm, the diameter is 20 μm, and the recess spacing is 150 μm.
[0090] According to the battery design requirements, multiple pole ears are designed. The pole ears can be circular, rectangular or other shapes, and are evenly distributed on the edge or surface of the pole piece. And welding, riveting or bonding methods are used (in this embodiment, the shape of the pole ear is rectangular and is fixed on the pole piece by rolling), and each pole ear is fixed at the corresponding position of the pole piece. The number of pole ears is B1 (see Table 3 for details).
[0091] 2) Negative electrode preparation
[0092] The negative electrode active material (artificial graphite and silicon-carbon negative electrode material, in which the mass of silicon element accounts for F% of the total mass of the negative electrode active material, see Table 3 for details), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 97:1:0.5:1:0.5, deionized water was added, and a negative electrode active slurry (solid content 65%) was obtained under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil (coating amount 0.17 g / 1500 mm 2 ), the coated copper foil is dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet. According to the battery design requirements, multiple pole ears are designed. The pole ears can be circular, rectangular or other shapes, and are evenly distributed on the edge or surface of the pole sheet. And welding, riveting or bonding methods are used (in this embodiment, the shape of the pole ear is rectangular and is fixed to the pole sheet by rolling), and each pole ear is fixed to the corresponding position of the pole sheet. The number of pole ears is B2 (see Table 3 for details).
[0093] 3) Preparation of isolation membrane
[0094] A polyethylene isolation film with a thickness of 7-9 μm is selected. In this embodiment, the thickness of the isolation film is 8 μm.
[0095] 4) Preparation of electrolyte: refer to Example 1.
[0096] 5) Preparation of lithium-ion batteries
[0097] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the isolation film of step 3) are stacked in the order of positive electrode sheet, isolation film and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, 8.5g of the electrolyte of step 4) is injected into the outer packaging, and a lithium-ion battery (capacity 5000mAh) is obtained after vacuum packaging, standing, formation, shaping, sorting and other processes.
[0098] Example E2-Example E16
[0099] The difference from Example E1 is that the composition of the electrolyte is different. The composition of the electrolyte in Example E2 to Example E16 corresponds to that in Example 2 to Example 16, respectively.
[0100] Example E17-Example E18
[0101] The difference from Example E1 is that the number B of tabs is different, see Table 3 for details.
[0102] Example E19-Example E26
[0103] The difference from Example E1 is that the depth, diameter and spacing of the recessed portion of the positive electrode sheet are different, as shown in Table 3 for details.
[0104] Example E27-Example E34
[0105] The difference from Example E1 is that the mass percentage F% of silicon element in the negative electrode active material is different, see Table 3 for details.
[0106] Comparative Example E1-Comparative Example E4
[0107] The difference from Example E1 is that the composition of the electrolyte is different. The composition of the electrolyte in Comparative Examples E1 to E4 corresponds to Comparative Examples 1 to 4, respectively.
[0108] Table 3
[0109]
[0110]
[0111] The performance of the lithium-ion batteries provided in the above embodiments and comparative examples was tested. The specific test results are shown in Table 4:
[0112] Table 4
[0113]
[0114]
[0115] From the data in the above table, it can be seen that when DFEA and pyridazine compounds are used as electrolyte solvents together, the electrolyte has a higher conductivity and enhanced antioxidant capacity. The electrolyte can remain stable for a long time, and the battery's long-term cycle capacity decreases less. Combined with the limitations on the electrode porosity, the number of tabs, and the silicon content in the negative electrode active material, the battery performance can be further improved. When each parameter is within the specified preferred range, the effect is better.
[0116] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. An electrolyte, characterized in that: include: Pyridazine compounds and difluoroethyl acetate, wherein the pyridazine compounds account for A% of the total mass of the electrolyte, 2≤A≤70; and the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 2≤D≤30.
2. The electrolyte according to claim 1, characterized in that The pyridazine compound accounts for A% of the total mass of the electrolyte, 5≤A≤30; And / or, the difluoroethyl acetate accounts for D% of the total mass of the electrolyte, 5≤D≤20.
3. The electrolyte according to claim 1 or 2, characterized in that The pyridazine compound has the following structure: Wherein, R1, R2, R3, R4 are independently selected from at least one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aromatic, substituted or unsubstituted carbonyl, and substituted or unsubstituted ester.
4. The electrolyte according to claim 3, characterized in that The pyridazine compound has any of the following structures:
5. A lithium ion battery, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 1 to 4.
6. The lithium-ion battery according to claim 5, characterized in that: It comprises an electrode sheet and a diaphragm, wherein B electrode tabs are arranged in the length direction of the electrode sheet, where B≥3; preferably, 3≤B≤50.
7. The lithium-ion battery according to claim 6, characterized in that: The electrode sheet has two surfaces arranged opposite to each other in its thickness direction, at least one of which is provided with a plurality of recesses, the depth of the recesses is 1-150 μm, the diameter is C μm, 5≤C≤100, and the spacing between the recesses is 20-500 μm.
8. The lithium-ion battery according to claim 7, characterized in that: The relationship between the diameter C μm of the concave portion and the percentage of the pyridazine compound in the total mass of the electrolyte A% satisfies the following equation: 0.5≤C / A≤20.
9. The lithium ion battery according to claim 7 or 8, characterized in that: The electrode sheet comprises a positive electrode sheet and a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material, the negative electrode active material contains silicon, and the mass percentage of silicon in the negative electrode active material is F%, 1≤F≤30; preferably, 5≤F≤20.
10. An electrical device, characterized in that: A lithium ion battery comprising any one of claims 5 to 9.
Citation Information
Patent Citations
Electrolyte and lithium-ion battery comprising same
CN105489935A
Electrolyte additive, electrolyte and lithium ion battery
CN113013491A
Lithium ion battery electrolyte and lithium ion battery
CN117254103A
Electrolyte, secondary battery containing electrolyte, battery pack and electric equipment
CN117878408A
Electrolyte of secondary battery, secondary battery and electronic device
CN118867399A